Correlation of the coach`s qualities and junior athletes` self-efficacy - Halian, I.; Popovych, I.; Vovk, V.; Kariyev, A.; Poleshchuk, L.; Halian, O. (Journal of Physical Education and Sport, 2023)
The purpose is to examine correlations between the coach`s personal and professional qualities and junior athletes with different levels of self-efficacy (n=103). Methods: correlation and cluster analyses, valid psycho diagnostic methods, coefficients for establishing statistical significance. Results. Self-efficacy was studied as a factor of successfulness in sporting activities and an indispensable component of professional training for junior athletes. The meaning of "subject activity" (SA) and "interpersonal communication" (IC) as components of junior athletes` self-efficacy was examined. A statistically significant correlation (p<.05; p<.01) of the coach`s qualities and SA (t = -11.905; p=.000) and IC (t = -2.222; p=.040) was established. There were statistically significant differences in manifestation of self-efficacy of the junior athletes in Group 1 and Group 2 by scale SA (t = -11.905; p=.000); Group I and Group II by scale IC (t = -2.222, p=.040). The research shows that athletes` evaluation of the coach`s personal and professional qualities is an important factor in the formation of self efficacy both in the area of "subject activity" and in the area "interpersonal communication". Junior athletes with a high level of self-efficacy by the criterion SA (Group 1) and IC (Group I) evaluate the coach`s personal and professional qualities at a high level by the following parameters: the gnostic parameter (M1=5.78±.66; M2=5.00±.866); the emotional parameter (M1=6.22±1.98; M2=7.33±.707); the behavioral parameter (M1=6.56±1.59; M2=6.8±1.33). Junior athletes with a low level of self-efficacy by the criterion SA (Group 2) and IC (Group M1) evaluated the coach`s role in their success in the following way: the gnostic parameter (M1=3.64±.505; M2=4.27±.1.42); the emotional parameter (M1=5.22±1.37; M2=4.18±.603); the behavioral parameter (M1=5.0±1.48; M2=4.64±.1.12). Pearson`s (R) correlation analysis allowed finding that evaluation of the coach`s professional qualities (R= 259; p<.01) and relationships between junior athletes and the coach (R=.178; p<.05) are important for the formation of self-efficacy related to sport qualification upgrading SA. The development of self-efficacy related to interpersonal communication IC depends on affection for the coach`s personality (R=.301; p<.01) and real relationships between junior athletes and the coach (R=.261; p<.01). Conclusions. It is generalized that the understanding of the role of the coach`s personal and professional qualities in increasing self-efficacy will contribute to better organization of sports pedagogical process, the development of skills in mutual constructive activity for achieving high sport results. Research on relationships "coach athletes" is considered to be promising in the context of improving the coach`s qualification and the formation of "team self-efficacy" in young athletes.